Optimal convergence velocity of V. I. Lebedev’s method on certain classes of operator equations - Sinenko , M. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Upper and lower estimates are obtained for the rate of convergence of V. I. Lebedev's method on certain classes of operator equations of the second kind.